Neutrality and the Dutch Objection Procedure - Marc Wever; Albert T. Marseille (Central European Public Administration Review)
In the Netherlands, if someone disagrees with an administrative order, he is only allowed to seek redress with the administrative courts after he has lodged an objection with the administrative authority responsible for the order. The objection procedure entails that an administrative body reconsiders its own decision. In this contribution we study the preference of objectors concerning the organization of the procedure and to what extent their preference is related to the perceived (lack of) neutrality of the person who conducted their hearing. In particular we focus on the effects of the use of neutral ‘outsiders’ when conducting hearings. Based on the literature we assumed that the use of outsiders would benefit the experienced impartiality of the person(s) conducting the hearing. The results of two discussed studies however do not support this assumption. The formal status of the persons conducting the hearing is a poor predictor of the extent to which they are perceived as neutral by participants of the procedure.